Ophthalmology review of patients with down syndrome: audit of local experience in a district hospital. (24th May 2012) - Ogundele, MO; Ayyash, HF; Pantush, T; Kostakis, A
Abstract : Background and aims: There is a high prevalence of ocular disorder among people with Down syndrome (DS). At least one third will have ocular/visual defects by two years of age. Refractive errors and/or squint may be present from an early age and persist into childhood. We aimed to review local clinical practice in terms of Ophthalmology review of patients with DS, compared to the Clinical Guideline of the Down Syndrome Medical Interest group - DSMIG (UK). Methods: A retrospective analysis of all DS patients identified on the hospital computer system was carried out. Data collected for each patient included age at diagnosis, current age, frequency of ophthalmology review, types of eye examination performed, diagnosis of any ophthalmology problems. We documented the nature and types of ocular examinations performed and of ocular pathologies identified in patients with DS. Results: A total of 43 patients (15 girls and 28 boys) with DS and mean age was 9 years 7 months (ranging from 2 weeks to 20 years). All patients were diagnosed either at birth or antenatally except in one case with mosaic trisomy 21 diagnosed at the age of 16 years. 12/43 (28%) did not have any ophthalmology review. Mean age at referral to the ophthalmologist for the remaining 31 patients was 3 years 5 months. The frequency of ophthalmology review varied between 2 months and over 6 years (mean of 2 years). The highest rate of compliance with the DSMIG recommendations was the newborn examination (88%). The rate of compliance at other age categories ranged between 37% and 53%. The commonest ocular abnormalities were Hyperopia 21 (64%), Astigmatism 12 (36%) and Strabismus or Exotropia 8 (24%) and Myopia 6 (18%) (figure 1 ). Conclusion: This study confirms that ocular abnormalities are common in patients with DS. A multi-disciplinary local clinical protocol has been agreed to improve compliance rate of the local ophthalmic surveillance in line with the national DSMIG recommendations.